2017
DOI: 10.1021/jacs.6b11626
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Azoheteroarene Photoswitch Performance through Heteroaryl Design

Abstract: Photoswitchable compounds, which can be reversibly switched between two isomers by light, continue to attract significant attention for a wide array of applications. Azoheteroarenes represent a relatively new but understudied type of photoswitch, where one of the aryl rings from the conventional azobenzene class has been replaced with a five-membered heteroaromatic ring. Initial studies have suggested the azoheteroarenes-the arylazopyrazoles in particular-to have excellent photoswitching properties (quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
429
3
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(464 citation statements)
references
References 59 publications
26
429
3
6
Order By: Relevance
“…9 Fuchter et al recently reported arylazopyrrole and arylazopyrazole photoswitches, which in some cases show long thermal half-lives and quantitative Z → E photoswitching. 10 Related arylazopyrazoles were used by Ravoo et al in switchable supramolecular host–guest systems. 11 Although several methods have been reported for the synthesis of (substituted) azobenzenes, 12 high-yielding entries into new classes of azoheterocycles are desirable.…”
mentioning
confidence: 99%
“…9 Fuchter et al recently reported arylazopyrrole and arylazopyrazole photoswitches, which in some cases show long thermal half-lives and quantitative Z → E photoswitching. 10 Related arylazopyrazoles were used by Ravoo et al in switchable supramolecular host–guest systems. 11 Although several methods have been reported for the synthesis of (substituted) azobenzenes, 12 high-yielding entries into new classes of azoheterocycles are desirable.…”
mentioning
confidence: 99%
“…Calculated geometries (see Supporting Information, Sections S16.1–16.3 for computational details and Table S23) show for each of 1 – 3 that the Z isomer has a twisted (nonplanar) conformation in the ground state. Fuchter and co‐workers have previously shown that substituents (or atoms with lone pairs) in the ortho position to an azo group can lead to such twisted configurations, which do not benefit from stabilizing dispersive interactions in the Z isomer. This suggests that the related unsymmetrical compounds in which one side of the azo bond is replaced with a phenyl ring could have considerably longer half‐lives, although potentially at the expense of the visible‐light photoswitching.…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation for a period of 30–60 s is sufficient to convert the trans form to the cis form, and λ =395 nm light seemed more effective on both compounds because isomerization under λ =395 nm irradiation was faster than with λ =365 nm light (Figures S1 and S2), thus λ =395 nm was set as irradiation wavelength for the photoisomerization of the compounds. The spectrum of the cis isomer was estimated based on the trans spectrum and cis ‐rich photostationary states (PSS, Figures B and D).…”
Section: Figurementioning
confidence: 99%